Rancang Bangun Sistem My-Vendor dalam Proses Pengadaan Barang Kebutuhan Kapal Berdasarkan Spesifikasi dan Harga pada PT. Serasi Shipping Indonesia - Ghedza Natava Blesynky Exzin; Rizqi Aini R; Edi Kurniawan; Romanda Annas Amrullah (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2024)
PT Serasi Shipping Indonesia is a company operating in the field of transportation and ship agency. Based on the results of observations during land-based practice in related research, researchers found several obstacles that could cause low effectiveness and gaps in the process of procuring goods on ships. Some of the problems that occur are that in the procurement process goods often have to arrive so that it has less impact on time effectiveness. Apart from that, the participating vendors do not comply with the company's SOP, so price conditions often occur. Based on these problems, an innovation is needed to overcome these problems with the existence of My Vendor. This research was developed using the Software Development Life Cycle (SDLC) method. The results of the application design are intended for 3 main user parties, namely PT Serasi Shipping Indonesia, PT Teknik Samudra Indonesia, and PT Thufail Segara Tama. The results of this research are in the form of an application design that has been integrated into the procurement process for necessary goods. The design and build process has 6 stages, namely planning, development, system design, implementation, testing and application maintenance. The researcher carried out 2 tests, namely using User Acceptance Testing (UAT) and obtained program correctness function results and output of 100%. Apart from that, based on the results of the usability function, the percentage of feasibility for the accumulated presentation was 95 percent. This means that the design that has been created is suitable for use. With the proposed digitalization system, it is hoped that it can become a bridge to solving problems based on appropriate trials. Apart from that, researchers hope that the proposed application will not only be for one company but will later be developed more widely for other companies and become a more useful and efficient business opportunity.